Uneven metabolic and lipidomic profiles in recovered COVID‐19 patients as investigated by plasma NMR metabolomics. (27th October 2021) - Bizkarguenaga, Maider; Bruzzone, Chiara; Gil‐Redondo, Rubén; SanJuan, Itxaso; Martin‐Ruiz, Itziar; Barriales, Diego; Palacios, Ainhoa; Pasco, Samuel T.; González‐Valle, Beatriz; Laín, Ana; Herrera, Lara; Azkarate, Aida; et al.
Abstract : COVID‐19 is a systemic infectious disease that may affect many organs, accompanied by a measurable metabolic dysregulation. The disease is also associated with significant mortality, particularly among the elderly, patients with comorbidities, and solid organ transplant recipients. Yet, the largest segment of the patient population is asymptomatic, and most other patients develop mild to moderate symptoms after SARS‐CoV‐2 infection. Here, we have used NMR metabolomics to characterize plasma samples from a cohort of the abovementioned group of COVID‐19 patients ( n  = 69), between 3 and 10 months after diagnosis, and compared them with a set of reference samples from individuals never infected by the virus ( n  = 71). Our results indicate that half of the patient population show abnormal metabolism including porphyrin levels and altered lipoprotein profiles six months after the infection, while the other half show little molecular record of the disease. Remarkably, most of these patients are asymptomatic or mild COVID‐19 patients, and we hypothesize that this is due to a metabolic reflection of the immune response stress. Abstract : We have used NMR‐based metabolomics to characterize plasma samples from a cohort of recovered COVID‐19 patients, six months on average after diagnosis. Our results show that half the patient population have abnormal metabolism and altered lipoprotein profiles while the other moiety shows little molecular record of the disease.